Knowledge on sexual health and its relationship with sexual behavior in university students - Ordoñez Sánchez, Joe (2018)
Introduction: Sexual and reproductive health is of great importance and is defined as a process linked to human development; That is, it begins at birth and develops throughout life. Objective: To establish the knowledge about sexual health and its relationship with sexual behavior of students in the ages of 18 to 25 years of the Faculty of Health Sciences of the Technical University of Babahoyo, year 2014. Design: non-experimental, transversal, comparative descriptive type. Place: Faculty of Health Sciences of the Technical University of Babahoyo Province of Los Ríos, Ecuador. Participants: Comprised 140 students from the schools of obstetrics and nursing. Interventions: A direct face-to-face interview using a validated questionnaire of the Integrated Project: "Sexual health and reproductive health of the student population of the National University of Costa Rica" was used. Measures of results: For the analysis the descriptive and analytical indicators between the variables were used. Results: The majority of students (92%) declared themselves to be sexually active, while 76% had oral sex. As for the attitude 50% of the students disagree that the men who are more adjusted are effeminate while 81% disapprove that women who do not care about their appearance are tomboy. Conclusions: Students are mostly sexually active and three out of four students practice oral sex, presenting a medium level of knowledge and behavior.